2004
DOI: 10.1021/jp048035z
|View full text |Cite
|
Sign up to set email alerts
|

Tautomerism in Hydroxynaphthaldehyde Anils and Azo Analogues:  a Combined Experimental and Computational Study

Abstract: The enol imine a enaminone tautomerization constants, K T , and thermodynamic parameters, ∆H T and ∆S T , of 1-hydroxy-2-naphthaldehyde Schiff bases are determined by UV/vis spectroscopy. Polar solvents shift the equilibrium toward the quinone form (for the unsubstituted derivative 1c, K T ) 0.20 (cyclohexane) and K T ) 1.49 (ethanol)). Both donor (MeO, NMe 2 ) and acceptor (CN, NO 2 ) substituents lead to a decreased K T independent of solvent polarity. In apolar solvents, for all derivatives 1a-1e, the enol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
93
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 156 publications
(100 citation statements)
references
References 116 publications
7
93
0
Order By: Relevance
“…The tautomeric constants in CHCl 3 and DMSO are 0.72 and 0.85 correspondingly, which is surprising taking into account the different proton acceptor/donor properties of these solvents. However, it has been proven by linear solvation energy relationship analysis [9] and by quantum chemical calculations [24] that due to the substantial strength of the intramolecular hydrogen bonding in the Schiff bases their interaction with proton acceptor solvents (like DMSO) is limited and the observed limited (in comparison with CHCl 3 ) changes result only from the net polarity of DMSO.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tautomeric constants in CHCl 3 and DMSO are 0.72 and 0.85 correspondingly, which is surprising taking into account the different proton acceptor/donor properties of these solvents. However, it has been proven by linear solvation energy relationship analysis [9] and by quantum chemical calculations [24] that due to the substantial strength of the intramolecular hydrogen bonding in the Schiff bases their interaction with proton acceptor solvents (like DMSO) is limited and the observed limited (in comparison with CHCl 3 ) changes result only from the net polarity of DMSO.…”
Section: Resultsmentioning
confidence: 99%
“…The salicylidene anilines (similar to compound 1 in the scheme below), being relatively simple in structure, are suitable model compounds for the study of the intramolecular proton transfer, and have therefore attracted considerable attention from both experimental [7][8][9] and theoretical [9,10] points of view. The proportioning between the tautomeric forms (enol E and keto K), which strongly depends on the conditions of the experimental/theoretical measurements, is the key moment in all investigations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that it exists under azoenol (AZO) and ketohydrazone (HYZ) forms ( Fig. 1) (15)(16)(17)(18)(19)(20). In a water solution, for example, the H-atom within the O-H .…”
mentioning
confidence: 99%
“…The inclusion complexes of OII and CDs have been studied by several groups showing the formation of a 1:1 entity (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). So far, the CD inclusion complex studies have considered that OII in water solutions exists under AZO tautomer, contrary to many studies in solutions where OII coexists under AZO and HYZ forms (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Recently, ultrafast transient lens technique with a response function of Ϸ300 fs has been used to study the dynamics of OII in CD (36).…”
mentioning
confidence: 99%